Position control under simultaneous limited torque and speed of a torque-driven nonlinear rotational mechanism. Issue 1 (31st December 2016) - Salinas, Adriana; Kelly, Rafael; Moreno-Valenzuela, Javier
Abstract : This paper deals with shaft displacement regulation (position control) of a torque-driven nonlinear gravity unbalanced mechanism under both prescribed bounded torque and speed. This is a novel control objective formulation for mechanisms. A nonlinear dynamic controller to resolve this control formulation is proposed. This controller aims to take care of the actuator/plant by keeping them within a safe operating torque–speed zone. An experimental study complements the proposed theory. Potential applications of the proposed approach are in safe control of robots.